2022
DOI: 10.1002/cne.25329
|View full text |Cite
|
Sign up to set email alerts
|

Coronal brain atlas in stereotaxic coordinates of the African spiny mouse, Acomys cahirinus

Abstract: The African spiny mouse (Acomys cahirinus) is an emerging model of mammalian epimorphic regeneration that has aroused the interest of the scientific community in the last decade. To date, studies on brain repair have been hindered by the lack of knowledge on the neuroanatomy of this species. Here, we present a coronal brain atlas in stereotaxic coordinates, which allows for three-dimensional identification and localization of the brain structures of this species. The brain of 12-week-old spiny mice was mapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…4 ). These tissue sections spanned a-p coordinates of + 1.5 mm To + 1.78 mm from bregma and d-v coordinates of − 4.4 to − 3.0 mm from the top of cortex based on a recent stereotaxic atlas 79 Note that hodological evidence of the division of the LS is lacking in spiny mice, however studies in numerous species have demonstrated that there is anatomical and functional subdivision of the LS with strong consistency in dorsal and ventral subdivision in rodents 80 . Thus, while we capture the dorsal and ventral portions of the LS of spiny mice, we acknowledge that future studies may further refine these subdivisions.…”
Section: Methodsmentioning
confidence: 99%
“…4 ). These tissue sections spanned a-p coordinates of + 1.5 mm To + 1.78 mm from bregma and d-v coordinates of − 4.4 to − 3.0 mm from the top of cortex based on a recent stereotaxic atlas 79 Note that hodological evidence of the division of the LS is lacking in spiny mice, however studies in numerous species have demonstrated that there is anatomical and functional subdivision of the LS with strong consistency in dorsal and ventral subdivision in rodents 80 . Thus, while we capture the dorsal and ventral portions of the LS of spiny mice, we acknowledge that future studies may further refine these subdivisions.…”
Section: Methodsmentioning
confidence: 99%